The iGPI collaborative project: moving IAM from science to industry - Leitão, J. P. (2014)
iGPI, the National Initiative for Infrastructure Asset Management (April 2012 - October 2013), is a Portuguese collaborative project led by LNEC (National Civil Engineering Laboratory, Portugal) through which 19 water utilities develop their own IAM systems and plans through a joint training and capacitation programme. Technical assistance to the participating utilities is ensured by LNEC, by a team from IST (Technical University of Lisbon) and by Addition, a software development company. The water utilities get collective as well as one-on-one support, specific training, and benefit from networking with the other utilities in a common and simultaneous process, with similar difficulties and challenges, leading to an effective sharing of solutions. The developed products, including training materials, templates and guidelines for developing strategic and tactical IAM plans, are available to the general public. This project has greatly contributed to the establishment of reference methodologies and standards for IAM planning, demonstrated in a range of utilities of widely diverse size and context, effectively defining an accepted best practice. This paper discusses the project’s format and its advantages, and goes on to describe the main outcomes, including selected cases and final products.